Cellulose Nanomaterials in Biomedical, Food, and Nutraceutical Applications: A Review. Issue 1 (16th August 2018) - Amalraj, Augustine; Gopi, Sreeraj; Thomas, Sabu; Haponiuk, Józef T.
Abstract : Nanotechnology with bionanomaterials have tremendous potential to enhance and utilize for nutrient and bioactive absorption, drug delivery systems, pharmaceutical, and nutraceutical field through various applications. Cellulose nanomaterials are green materials that are obtained from renewable sources and possess exceptional mechanical strength and biocompatibility. The associated unique physical and chemical properties have made various nanocomposite materials an intriguing prospect for different application in the biomedical, food, and nutraceutical industries. In this review, we have discussed and provided a summary of the recent researches in the utilization of cellulosic nanomaterials in applications related to food packaging, bone tissue engineering, wound dressing, drug delivery, and nutraceutical research area and industries.